2004
DOI: 10.1152/ajpgi.00246.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin regulation of ferroportin 1 expression in the liver and intestine of the rat

Abstract: Hepcidin has been implicated as the iron stores regulator: a hepatic signaling molecule that regulates intestinal iron absorption by undefined mechanisms. The possibility that hepcidin regulates the expression of ferroportin 1 (FPT1), the basolateral iron transporter, was examined in rats after administration of LPS, an iron chelator, or His-tagged recombinant hepcidin (His-rHepc). In the liver, LPS stimulated a biphasic increase of hepcidin mRNA with peaks of mRNA at 6 and 36 h. Concurrently, hepatic FPT1 mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 44 publications
(61 reference statements)
10
65
0
Order By: Relevance
“…The iron exporter ferroportin has been shown both to regulate cellular iron uptake by binding to hepcidin (3) and to be transcriptionally downregulated by high hepcidin levels (28). Consistent with the observed lack of hepcidin expression in Hjv-mutant mice, we found high expression of ferroportin in both untreated and sham-injected Hjv-mutant mice ( Figure 4B and data not shown).…”
Section: Generation Of Hjv-mutant Mice and Expression Of Hjv In Peripsupporting
confidence: 87%
See 1 more Smart Citation
“…The iron exporter ferroportin has been shown both to regulate cellular iron uptake by binding to hepcidin (3) and to be transcriptionally downregulated by high hepcidin levels (28). Consistent with the observed lack of hepcidin expression in Hjv-mutant mice, we found high expression of ferroportin in both untreated and sham-injected Hjv-mutant mice ( Figure 4B and data not shown).…”
Section: Generation Of Hjv-mutant Mice and Expression Of Hjv In Peripsupporting
confidence: 87%
“…LPS (1 µg/g body weight; serotype O111: B4; Sigma-Aldrich), IL-6 (12.5 ng/g body weight; R&D Systems), and TNF-α (12.5 ng/g body weight; R&D Systems) were injected intraperitoneally, and organs were isolated for RNA preparation 6 hours after LPS and 4 hours after IL-6 and TNF-α injections (28). Iron-dextran or PBS/dextran/phenolcontrol solution was injected subcutaneously as previously described, and animals were analyzed 7 days after injection (8).…”
Section: Methodsmentioning
confidence: 99%
“…Yeh et al have reported that Fpn transcripts are unaltered in the livers of iron-deficient Belgrade rats (in which hepcidin expression is dramatically decreased); these investigators also observed that systemic administration of recombinant hepcidin to rats failed to modify hepatic Fpn mRNA levels. 33 We have found that both Fpn and DMT1 mRNA are increased in the livers of C57Bl6 mice fed a high fat diet or chronically administered 20% ethanol in the drinking water. In neither of these models of fatty liver does the expression of the iron transporters correlate with HAMP mRNA or HIC (O Bergmann and K Brown, in preparation).…”
Section: Iron Regulatory Genes In Cirrhosismentioning
confidence: 82%
“…Intraperitoneal injection of bacterial endotoxin (lipopolysaccharide [LPS]) and subcutaneous injection of turpentine were shown to increase hepcidin gene expression in mice. 8,13,14 Inflammation-induced hepcidin gene expression has also been reported in other animal models, including humans, suggesting that hepcidin is a key mediator of anemia of inflammation. 15,16 Cytokines, primarily interleukin 1 (IL-1), tumor necrosis factor ␣, and IL-6, are involved in the regulation of systemic (LPS) and localized (turpentine) inflammation.…”
mentioning
confidence: 86%